Two sides to every leaf: water and CO₂ transport in hypostomatous and amphistomatous leaves - Drake, Paul L.; de Boer, Hugo J.; Schymanski, Stanislaus J.; Veneklaas, Erik J. (The New phytologist, 2019)
Leaves with stomata on both upper and lower surfaces, termed amphistomatous, are relatively rare compared with hypostomatous leaves with stomata only on the lower surface. Amphistomaty occurs predominantly in fast-growing herbaceous annuals and in slow-growing perennial shrubs and trees. In this paper, we present the current understanding and hypotheses on the costs and benefits of amphistomaty related to water and CO₂ transport in contrasting leaf morphologies. First, there is no evidence that amphistomatous species achieve higher stomatal densities on a projected leaf area basis than hypostomatous species, but two-sided gas exchange is less limited by boundary layer effects. Second, amphistomaty may provide a specific advantage in thick leaves by shortening the pathway for CO₂ transport between the atmosphere and the chloroplasts. In thin leaves of fast-growing herbaceous annuals, in which both the adaxial and abaxial pathways are already short, amphistomaty enhances leaf–atmosphere gas-exchange capacity. Third, amphistomaty may help to optimise the leaf-interior water status for CO₂ transport by reducing temperature gradients and so preventing the condensation of water that could limit CO₂ diffusion. Fourth, a potential cost of amphistomaty is the need for additional investments in leaf water transport tissue to balance the water loss through the adaxial surface.